Homoseksualność – społeczeństwo, język, tożsamość - Majka-Rostek, Dorota (2022)
The article concerns homosexuality as a social phenomenon, constructed and regulated by cultural definitionand norms. Historical changes of these definitions go hand in hand with the evolution of social sciences’ approachto non-normative sexualities. These transformations are reflected in language, which in turn heavily influencethe processes of constructing sexual identities. This article presents excerpts from research which illustrates theaforementioned phenomena. The research consisted of biographic-narrative interviews with gay men who built thecore of their sexual identity in times of Polish People‘s Republic, where available language resources were more ofa barrier than aid in such processes.
Keywords: homosexuality; language; society; sexual identity